Development of Steam-Based E-Booklets to Improve IPA Learning Outcomes on Human Respiratory System Material in Class V Sdn 104208 - Arpah, Siti; Hasruddin; Hadi, Wisman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to determine the validity, practicality, and effectiveness of STEAM-based e-booklets in science lessons on human respiratory system material. This type of research is an ADDIE model of development research (analysis, design, development, implementation, and evaluation). Data collection techniques in this study were observation, interviews, validation, and tests. This research was conducted in class V, SDN 104208, Cinta Rakyat. The results of this study indicate that (1) the product is valid from media expert I by 90% and expert II by 84%. (2) The product is valid according to material expert I by 86% and material expert II by 93%. (3) The product is valid according to language experts by 90.7%. (4) The product received a positive response from users, namely 2 V-A class teachers by obtaining 93.4%, V-B class teachers obtained a percentage of 94.7%, and students as product practicality experts. (5) The effectiveness test with the percentage of learning completeness is shown using the t test results (2-tailed), which are obtained at 0.000 referring to the basis for decision-making means 0.000 <0.05 or Ho is rejected and H1 is accepted. Thus, it is concluded that there is an influence between STEAM-based e-booklets and student learning outcomes on the material of the respiratory system in humans in grade V students of SDN 104208 Cinta Rakyat and STEAM-based e-booklets are proven to be effective for the science learning process in grade V.